Anticoagulation Current Perspectives - Qi, Xingshun; Guo, Xiaozhong (IntechOpen, 2022)
Thrombotic diseases are some of the leading causes of death in the world. Anticoagulation is a mainstay approach for the prophylaxis and treatment of thrombotic diseases. This book includes six chapters regarding the mechanisms of anticoagulation and its clinical value in different disease conditions. The first two chapters summarize the general information regarding anticoagulation and hypercoagulability/thrombophilia, and the remaining four chapters discuss the use of anticoagulation in different populations, including adult hospitalized surgical and medical patients, COVID-19 patients, patients with hepatic thrombotic disorders, and frail elderly patients with atrial fibrillation.